Pulmonology diseases: Bronchial asthma. Copd. Pneumonias. Diagnosis and management approaches - Vizir, V. A.; Berezin, A. E.; Візір, Вадим Анатолійович; Березін, Олександр Євгенійович; Писанко, Оксана Володимирiвна (ZSMU, 2015)
Executable task force is addressed to students o f 5-th and 6-th courses of medical university for helping to study of internal medicine according pulmonology diseases.